Intravesical wire as foreign body in urinary bladder - Dilip K. Pal; Asim K. Bag (International Brazilian Journal of Urology, 2005)
Foreign bodies in the urinary bladder are frequently the objects of jokes among doctors, but they may sometimes cause serious implications to the patients. Here we present our experiences in 3 such cases where long segments of wire were introduced into the urinary bladder through the urethra.